A duplicidade e a (re)construção do (sujeito) feminino na arte moderna: uma leitura da obra A cidade sitiada de Clarice Lispector - Santos, Erika da Silva (2024)
The object of this study is the novel published by Brazilian writer Clarice Lispector in 1948, The Besieged City. Firstly, an overview of Clarice's critical reception is presented, both in the midst of her emergence in our letters, seeking to demonstrate the renovations she had established, and during the publication of the plot analyzed here, whose objective is to make its constitutive richness visible, in view of the marginalization it had suffered in relation to the whole of Clarice's production. Subsequently, not only is the author's poetic construction analyzed, especially in terms of her work to renew language, but also the protagonist character of The City, Lucrécia, her trajectory, her relationships with different interactive pairs and new forms of (visual) apprehension of the Romanesque space, São Geraldo. In this sense, we seek to understand how the novel strained the horizon of expectation that its time attributed to modern literary production by women and how its character also challenged what was expected of women in literature